The art of empire in Achaemenid Persia : studies in honour of Margaret Cool Root - Dusinberre, Elspeth R. M.; Garrison, Mark B.; Henkelman, Wouter; Root, Margaret Cool (Achaemenid history, 2020)
"This volume in honour of Margaret Cool Root gathers seventeen contributions on Achaemenid Persian art, ranging from the European re-discovery of Persepolis, via Achaemenid glyphic art, evidence of polychrome sculpture, and Achaemenid impact in the satrapies, to possible reflections of Persepolitan art in Classical Greece. The contributors are colleagues and, in a number of cases, former students of Margaret Root. As a whole, the volume reflects the wide range of Root's interests and her impact on the field of Achaemenid studies.""--Publisher's description